Santalol Isomers Inhibit Transthyretin Amyloidogenesis and Associated Pathologies in Caenorhabditis elegans - Mohankumar, Amirthalingam; Kalaiselvi, Duraisamy; Thiruppathi, Govindhan; Muthusaravanan, Sivaramakrishnan; Vijayakumar, Subramaniam; Suresh, Rahul; Tawata, Shinkichi; Sundararaj, Palanisamy (Frontiers in Pharmacology, 2022)
Transthyretin (TTR) is a homotetrameric protein found in human serum and is implicated in fatal inherited amyloidoses. Destabilization of native TTR confirmation resulting from mutation, environmental changes, and aging causes polymerization and amyloid fibril formation. Although several small molecules have been reported to stabilize the native state and inhibit TTR aggregation, prolonged use can cause serious side effects. Therefore, pharmacologically enhancing the degradation of TTR aggregates and kinetically stabilizing the native tetrameric structure with bioactive molecule(s) could be a viable therapeutic strategy to hinder the advancement of TTR amyloidoses. In this context, here we demonstrated α- and β-santalol, natural sesquiterpenes from sandalwood, as a potent TTR aggregation inhibitor and native state stabilizer using combined in vitro, in silico, and in vivo experiments. We found that α- and β-santalol synergize to reduce wild-type (WT) and Val30Met (V30M) mutant TTR aggregates in novel C. elegans strains expressing TTR fragments fused with a green fluorescent protein in body wall muscle cells. α- and β-Santalol extend the lifespan and healthspan of C. elegans strains carrying TTRWT::EGFP and TTRV30M::EGFP transgene by activating the SKN-1/Nrf2, autophagy, and proteasome. Moreover, α- and β-santalol directly interacted with TTR and reduced the flexibility of the thyroxine-binding cavity and homotetramer interface, which in turn increases stability and prevents the dissociation of the TTR tetramer. These data indicate that α- and β-santalol are the strong natural therapeutic intervention against TTR-associated amyloid diseases.